Clinical and Urine Scoring in Assessing the Long-Term Outcome of Acute Kidney Injury/Acute Kidney Disease with risk of Progression to Chronic Kidney Disease - Saugat Das Gupta; Arpita Ray Chaudhury; Koushik Bhattacharjee; Atanu Pal; Abhishek Kumar; Smartya Pulai; Debabrata Sen; Keya Basu; Moumita Sengupta; Rajendra Pandey (Indian Journal of Kidney Diseases)
Background: Acute kidney disease (AKD) represents an important transition period for patients who have suffered an episode of acute kidney injury (AKI) and AKI is a significant risk factor for the development of chronic kidney disease (CKD). Materials and Methods: This is a single-center observational study conducted in the Department of Nephrology of a large tertiary care Nephrology center with 430 AKI patients from May 2019 to November 2020. The six-variable risk index score for advanced CKD using advanced CKD after AKI risk index and Urine cast scoring index were calculated for each patient. Scheduled follow-up visits for each participant were done during the subsequent 6 months. Results: Most patients were in the age group 21–30 years (23.5%), 55.3% were male, 76% were from a rural background, and 27.8% were smokers with the majority (62.7%) having community-acquired AKI. Ninety-seven percent were in KDIGO stage 3 with 88.8% being oligo-anuric at presentation. AKI was mostly due to medical causes (95.3%), amongst which the top three causes were snake bite (34.8%), tropical infection (15.3%), and sepsis (14%). Progression to AKD was seen in 85.8%. Patient recovery at discharge, 1 month, 3 months, and 6 months were 16.3%, 47.8%, 58.8%, and 60% respectively. In multivariate analysis peak creatinine and urine score were found to have significance with the recovery of renal function at 3 months; while only urine score was found significant with recovery at 6 months of follow-up. Conclusions: Snakebite, tropical infection, and sepsis still represent an important cause of renal replacement therapy requiring AKI in our part of the Indian subcontinent with a substantial proportion not recovering up to 6 months of follow-up and contributing to the overall CKD burden. Persistence of AKI or AKD should be a wake-up call for the clinician to further assess and evaluate treatment options to improve long-term outcomes. Combining comprehensive clinical evaluation with the use of “Risk scoring” and urine sediment analysis would provide new insights into AKI for better patient risk stratification and prognostication and resurrect the ancient tradition of looking at the urine to open the window of the body.